PENGARUH AUDIT TENURE DAN LOWBALLING TERHADAP PEMBERIAN OPINI AUDIT - Eka Fitri Yanti; Yulianti Yulianti; Amilin Amilin (Akuntabilitas, 2014)
The main purpose of this study was to examine the influence of audit tenure andlowballing to the appropriation of audit opinion. Based on convenience sampling method. Thisstudy used a sample of 61 respondents who work as auditor in audit firm located in Jakartaand enrolled in Directory AP & KAP 2013 published by IAPI. This study used primary data withquestionnaire. Auditor who participated in this research include partner, manager, supervisor,senior auditors and junior auditors who carry out work in the field of auditing The data wasanalyzed by multiple regression. The results indicates that the audit tenure didn’t have aninfluence to the present of audit opinion. But lowballing had influenced to the present of audit opinionDOI: 10.15408/akt.v7i2.2676